Wacana (2017)
WACANA Journal publishes scientific papers on the research and scientific studies in the scope of humanities and social studies, such as anthropology, studies, business, communication studies, corporate governance, criminology, the study of cross-cult
ural, demographic, economic studies of development, the study of education and ethics, social geography, the study of information technology management, industrial relations, international relations, legal studies, media studies, political science, th
e study of population dynamics, the study of psychology, the study of public administration, social welfare, religious studies and linguistics.